Between fame and shame: performing women - women performers in India - Brückner, Heidrun; Oberlin, Heike (Drama und Theater in Südasien, 2011)
Twelve essays dealing with the role of women in various Indian performance traditions and in different social contexts. The volume's contributions are intended to convey a better understanding of the often troubled relation between women and public performances. The cultural performances studied range from possession performed by women as a religious service to a deity, to on-stage performances by professional actresses representing different performance genres. The regional focus is on South India, especially Kerala and Karnataka. A special feature of the book is the simultaneous internet publication of the audio, audio-visual, and visual materials referred to in the articles. Some of the audio provide for the first time samples of oral literary genres recorded, in some cases as early as the 1970s. The authors of the essays are anthropologists (Claus, Schö̈mbucher, Guillebaud), folklorists (Rai), Indologists (Brückner, de Bruin, Moser, Johan, Griebl/Sommer) sociologists (Schulze), and theatre scholars (Daugherty, Pitkow) from India, Europe, and the USA
Literaturangaben
Keywords: India -- Congresses; Konferenzschrift -- 2005 -- Würzburg; Geschlechterrolle; Darstellende Künstlerin; Kultur; Indien